2014
DOI: 10.1371/journal.pone.0104460
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixed By Cyanobacteria Is Utilized By Deposit-Feeders

Abstract: Benthic communities below the photic zone depend for food on allochthonous organic matter derived from seasonal phytoplankton blooms. In the Baltic Sea, the spring diatom bloom is considered the most important input of organic matter, whereas the contribution of the summer bloom dominated by diazotrophic cyanobacteria is less understood. The possible increase in cyanobacteria blooms as a consequence of eutrophication and climate change calls for evaluation of cyanobacteria effects on benthic community function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 49 publications
3
33
1
Order By: Relevance
“…It could also explain the generalized pattern of low δ 15 N values recorded in the Bay of Marseille, notably for zooplankton (Bănaru et al, 2014;Espinasse et al, 2014;Tiano et al, 2014). In the Baltic Sea, previous results confirmed that diazotrophic bacteria can be a significant food source for the whole trophic network (zooplankton and benthic invertebrates), since it can represent up to 80 % of the diet of some species (Karlson et al, 2014;Lesutienė et al, 2014). Assessing accurately the contribution of this source to the diet of suspension feeders, for example through their integration as an endmember in a mixing model, is nevertheless complex since it would require an accurate determination of δ 13 C value for diazotrophic bacteria in the bay of Marseille.…”
Section: Accepted Manuscriptmentioning
confidence: 69%
See 2 more Smart Citations
“…It could also explain the generalized pattern of low δ 15 N values recorded in the Bay of Marseille, notably for zooplankton (Bănaru et al, 2014;Espinasse et al, 2014;Tiano et al, 2014). In the Baltic Sea, previous results confirmed that diazotrophic bacteria can be a significant food source for the whole trophic network (zooplankton and benthic invertebrates), since it can represent up to 80 % of the diet of some species (Karlson et al, 2014;Lesutienė et al, 2014). Assessing accurately the contribution of this source to the diet of suspension feeders, for example through their integration as an endmember in a mixing model, is nevertheless complex since it would require an accurate determination of δ 13 C value for diazotrophic bacteria in the bay of Marseille.…”
Section: Accepted Manuscriptmentioning
confidence: 69%
“…A predominant integration of bacterial-derived OM could be another explanation for these rather low values. Diazotrophic bacteria have δ 15 N ratios close to 0 ‰ or even negative (Karlson et al, 2014;Briand et al, 2015) and are predominant in two terrigenous water inputs in the bay of Marseille (Huveaune River and wastewater outfall), with the low isotopic ratios of the wastewater outfall consistent with the predominance of diazotrophic bacteria (Bănaru et al, 2014). They are also abundant during summer blooms in the bay of Marseille (2 to 5 10 2 cells mL -1 , Le…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…Evidence is, however, accumulating that these cyanobacteria are eaten by many grazers, suspension-feeders, and deposit-feeders, often with beneficial effects on their growth and reproduction. In line with this, field studies show that organic matter and bioavailable nitrogen produced by these cyanobacteria are incorporated by pelagic, littoral, and benthic food webs (e.g., Rolff 2000 ; Karlson et al 2014 ; Lesutiene et al 2014 ), challenging the view that cyanobacteria do not contribute to secondary production. Moreover, grazing on toxic cyanobacteria is species-specific and influenced by many factors (e.g., toxin concentrations and availability of other prey), with concomitant feed-back effects on toxin production (Gorokhova and Engström-Öst 2009 ; Engström-Öst et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the peak value we recorded (δ 15 N = 4%) is lower than normally recorded values, the δ 15 N does record a steady increase over time, as expected. Results can be skewed by cyanobacteria that alter isotope ratios; for example, δ 15 N values can be depleted after cyanobacterial blooms due to uptake of diastrophic 14 N. In a study from the Baltic Sea, Karlson et al (2014) found that sediment δ 15 N values were depleted when compared to sediment values prior to a cyanobacterial bloom.…”
Section: Sediment Core and Paleolimnological Analysesmentioning
confidence: 99%